1988
DOI: 10.1002/mpo.2950160207
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of fine needle aspiration in the diagnosis and management of neuroblastoma

Abstract: Eleven fine needle aspiration (FNA) biopsies were performed in five children with neuroblastoma, including one patient with peripheral neuroectodermal tumor of the thoracopulmonary region (Askin tumor). Cytologic features in conjunction with immunocytochemistry and electron microscopy on the aspirated material enabled us to make a primary diagnosis in four of the five patients and diagnose local recurrence and metastatic disease in three patients. There were no false-positive or false-negative cytologic diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Fine needle aspiration biopsy identifies the presence of small cells with neurosecretory granules, microtubules, and cytoplasmic extensions. [6] Results of 123I-Tyr-3-Octeotride scintigraphy are positive for most of the tumors and metastasis. [7] Characteristics PENT pathologic findings include compact nests of small cells, Homer-Wright pseudo rosettes with an acidophilic core of neurofibrillar characteristics, and uptake of neuron specific enolase stain.…”
Section: Discussionmentioning
confidence: 99%
“…Fine needle aspiration biopsy identifies the presence of small cells with neurosecretory granules, microtubules, and cytoplasmic extensions. [6] Results of 123I-Tyr-3-Octeotride scintigraphy are positive for most of the tumors and metastasis. [7] Characteristics PENT pathologic findings include compact nests of small cells, Homer-Wright pseudo rosettes with an acidophilic core of neurofibrillar characteristics, and uptake of neuron specific enolase stain.…”
Section: Discussionmentioning
confidence: 99%
“…1,[3][4][5][6]8 In general, the cytologic features of ONB mimic those of conventional neuroblastoma. [9][10][11][12][13] Overall, authors found single cells and cell groups with a variable number of rosettes or pseudorosettes. On critical review of photomicrographs in the English-language literature, our case revealed true rosette formation as compared with previous cases.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor cells usually reveal large numbers of intertwining cytoplasmic processes containing longitudinally arranged microtubules and scattered neurosecretory granules. 1,4,[31][32][33][34] The tumor cells and cell processes have large synaptic cell junctions.…”
Section: Neuroblastoma (Nb)mentioning
confidence: 99%
“…C-6A). [30][31][32][33][34][35] The morphology of the smears may vary considerably, depending upon the degree of differentiation of neuroblastic cells. 36,37 Similar to the histologic classification, the tumors may be divided into undifferentiated, poorly differentiated, and differentiating NB.…”
Section: Neuroblastoma (Nb)mentioning
confidence: 99%